Pengayaan Wawasan Siswa Mengenai Perilaku Hidup Bersih dan Sehat (PHBS) di SD Selolembu Kabupaten Bondowoso - Wardhono, Adhitya; Qori’ah, Ciplis Gema; Nasir, M. Abd.; Prakoso, Bhim; Salsabila, Adelia Syahara; Nariswari, Septiya; Ramadhani, Nabila Fajrin Kurnia; Gontha, Chelsea Tiara; Tazkiya, Anisa; Puspito, Agung Nugroho (AJAD : Jurnal Pengabdian kepada Masyarakat, 2025)
The right age for children to be given education about health is 6 -14 years old because at this age children can receive information and understand the information provided quite well (1). This activity aims to increase elementary school students' awareness of clean living by providing PHBS education and growing awareness in consuming balanced nutrition food by providing education about isi piringku. This activity was carried out at SDN Selolembu, Curahdami District, Bondowoso Regency. The method of this activity is presentation, practice, and games related to the material provided. This social project has succeeded in increasing the insight of Selolembu Elementary School students regarding food that has balanced nutrition and the application of PHBS in daily life.